Jesting in Earnest : Percival Everett and Menippean Satire - Maus, Derek C. (Book collections on Project MUSE., 2019)
"When writing about Percival Everett, it has become customary to begin with a caveat that the conspicuous variety within his body of work will inherently frustrate any attempts at definitive classification. This selection of texts spans nearly the full length of Everett's career as a writer and includes his most popular works as well as some of his more obscure ones. It is intended as a sampling of the whole, not a ranked list; one should not infer from the emphasis on these fourteen works that Everett's remaining sixteen books are necessarily of lesser significance or lesser quality"--